(untitled) - Ong, Guek Ju (Singapore, 2013)
(3z(BFrom strength to strength(3y(B, it is obvious, that this is not for weaklings but those desirous to live life to the fullest by giving their utmost for His great purposes. A book to read and re-read!s
Keywords: Spiritual life -- Christianity